2016
DOI: 10.21276/aimdr.2016.2.6.me10
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Diabetic Retinopathy among DiabeticPatients in King Abdulaziz University Hospital, Jeddah,Saudi Arabia

Abstract: Background: Diabetic retinopathy is a serious complication of DM, it occurs due to poor control of DM and lack of knowledge on the complications of DM. Among many approaches, strong awareness of retinopathy by diabetic patients could help in the early detection, management and prevention of this complication. Aim: this study was conducted to assess the awareness of diabetic retinopathy among diabetics in Saudi Arabia. Methods: A hospital-based, cross sectional study was conducted using a pre-tested questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Results of this study showed that almost the half of diabetic patients attending King Salman Armed Forced Hospital-Primary Health Care had poor knowledge regarding retinopathy, while fourth of them had moderate knowledge, and (25%) had good knowledge. The levels of diabetic patients' knowledge regarding retinopathy have been reported by several studies, which are lower than Alasiri and Bafaraj study in Jeddah, reported that (61.0%) of diabetic patients had good knowledge about retinopathy [5]. A similar result was reported in Hail-Saudi Arabia, where the awareness level of DR showed a 76% awareness [6].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Results of this study showed that almost the half of diabetic patients attending King Salman Armed Forced Hospital-Primary Health Care had poor knowledge regarding retinopathy, while fourth of them had moderate knowledge, and (25%) had good knowledge. The levels of diabetic patients' knowledge regarding retinopathy have been reported by several studies, which are lower than Alasiri and Bafaraj study in Jeddah, reported that (61.0%) of diabetic patients had good knowledge about retinopathy [5]. A similar result was reported in Hail-Saudi Arabia, where the awareness level of DR showed a 76% awareness [6].…”
Section: Discussionmentioning
confidence: 61%
“…This result showed that it is well known that awareness is a vitally important step in the creation of a successful program to battle against any disease in the community [5].…”
Section: Discussionmentioning
confidence: 69%
“…[36] Another study from Jeddah, King Abdul Aziz University hospital reported awareness of DR among 61% of the patients. [37] Studies from different countries reported different level of knowledge about the eye disease caused by diabetes; in India, USA, and Oman there were 50%, 52% and 75% patients, respectively, who had awareness. [383940] The rates of awareness were higher in Myanmar and Nigeria, where the awareness rates were 86% and 84.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[33] A study from AlJouf and Hail province, KSA reported that 75.62% of diabetic patients were aware that diabetes can result in eye diseases. [34] A study from Taif, KSA showed that two-thirds of screened T2DM patients had good knowledge about DR.[35] A study from Jeddah, KSA demonstrated that DM patients had a good awareness about DM and its effects on eye; however, they showed the lack of awareness regarding DR.[36] Another study from Jeddah, King Abdul Aziz University found that 61% of diabetic patients had awareness about DR.[37]…”
Section: Introductionmentioning
confidence: 99%
“…There was a significant difference between patients with type 1 and type 2 diabetes regarding the level of awareness (63.8% vs. 36.2% respectively). Even though almost two-thirds of patients were aware of DR, only 50% had ever had an eye checkup, and only 19.8% were undergoing regular annual checkups [ 33 ].…”
Section: Reviewmentioning
confidence: 99%